2020
DOI: 10.1158/1535-7163.mct-20-0094
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Retrovirus Transcript Levels Are Associated with Immunogenic Signatures in Multiple Metastatic Cancer Types

Abstract: ◥Next-generation sequencing of solid tumors has revealed variable signatures of immunogenicity across tumors, but underlying molecular characteristics driving such variation are not fully understood. Although expression of endogenous retrovirus (ERV)-containing transcripts can provide a source of tumor-specific neoantigen in some cancer models, associations between ERV levels and immunogenicity across different types of metastatic cancer are not well established. We performed bioinformatics analysis of genomic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…In addition, the clinical variants annotated in the ERV regions coincide with variants associated with tumors, reinforcing the idea that the analyzed ERV sections have important roles in cell cycle regulation and their misregulation leads to cancer. In agreement with these observations, several authors have described an association between ERVs and cancer; moreover, this relationship is explained by ERV activation ( Ibba et al, 2018 ; Topham et al, 2020 ). Following our data, another possibility for disrupting the cell cycle and producing tumors could be through TFBS mutations that prevent TFs from binding to DNA.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, the clinical variants annotated in the ERV regions coincide with variants associated with tumors, reinforcing the idea that the analyzed ERV sections have important roles in cell cycle regulation and their misregulation leads to cancer. In agreement with these observations, several authors have described an association between ERVs and cancer; moreover, this relationship is explained by ERV activation ( Ibba et al, 2018 ; Topham et al, 2020 ). Following our data, another possibility for disrupting the cell cycle and producing tumors could be through TFBS mutations that prevent TFs from binding to DNA.…”
Section: Discussionsupporting
confidence: 76%
“…The SNPs themselves are in high LD and are spread out across the TET2 gene (although those associated with higher HIV-VL tend to congregate in the 5’ end of TET2). Given the previous evidence associating TET2 with transcriptional regulation of endogenous retroviral elements [ 29 31 ], it may be that TET2 is playing a role in transcriptional regulation of HIV. Alternatively, previously studies have suggested two independent mechanisms for TET2 related enhancement of HIV-VL, mediated through the VPR.…”
Section: Discussionmentioning
confidence: 99%
“…Here, TET and APOBEC genes-which are important to DNA demethylation pathways-were differentially expressed in all three cancer types. Previous work has associated TET2 overexpression with increased HERV expression and antiviral immune response signatures (27), suggesting a link between demethylation and HERV activation in cancer. TET2 was downregulated in COAD, while TET3 was upregulated in BRCA and PRAD, with TET1 also being upregulated in PRAD.…”
Section: Discussionmentioning
confidence: 96%
“…HERV expression has also been shown to contribute to immunomodulation of host cells and HERVs have been implicated in the regulation of innate immunity (25,26). Furthermore, a viral mimicry phenotype has been identified in subsets of metastatic tumors, which correspond to increased HERV expression, further suggesting the contribution of HERVs to inflammatory immune responses supporting tumor survival (27). Thus, an understanding of host cell factors including epigenetics and immunogenicity, in addition to HERV expression, is highly relevant to translational applications.…”
Section: Introductionmentioning
confidence: 99%